Design and manufacture of CubeSat-type nanosatellite thermal subsystem - Braulio Peraza-Acosta; Jesús Irán Grageda-Arellano; Carlos Couder-Castañeda; Jaime Meléndez-Martínez; Diego Alfredo Padilla-Pérez; Arturo Solis-Santome (Scientific Reports)
Abstract This work presents the design and validation of a thermal subsystem for a 1U CubeSat-type nanosatellite. The design encompasses two stages: regulating the satellite’s temperature range through implementing passive control based on multilayer coatings and an electronic board capable of measuring the internal surface temperature of each of the satellite’s six faces. Validation is conducted through tests performed in a theoretical thermo vacuum chamber that provides a controlled environment, simulating the thermal conditions to which the satellite will be exposed once in orbit. The data collected by the sensors on the electronic board are encapsulated and transmitted wirelessly in real-time to an Earth station, where they are processed and displayed through a graphical interface. This setup allows for assessing the effectiveness of the implemented passive control.